Antecedents and consequences of South African female athletes’ trust in the coach - Mashilo, Bontle; Kubayi, Alliance (Frontiers in Sports and Active Living, 2024)
The purpose of this study was to investigate female South African school athletes’ trust in their coaches in relation to their perceptions of the coaches’ justice, benevolence, integrity, competence, commitment to coach, willingness to cooperate, and performance. A quantitative cross-sectional research design was used in this study. The results showed that there was a large correlation between trust in the coach and the following factors: perceived justice (r = .504, p < .01), perceived integrity (r = .511, p < .01), and perceived competence (r = .534, p < .01). Furthermore, multiple regression analysis results revealed that perceived justice was the only signiﬁcant predictor of trust in the coach as it had a higher beta value (β = .17, p < .05) than the other variables. This study shows that coaches should demonstrate fairness in their decision-making by providing players with incentives, opportunities to play, friendly relationships, and places of preference.